Microstructural characterization of irradiation-induced MnNI-rich solute cluster in highly neutron-irradiated MnNiMo alloyed weld metals - Lim, J; Hyde, J; Lozano-Perez, S; Grovenor, C (ASTM International, 2014)
Maintaining the safe operation of nuclear power plants (NPPs) is crucial. This requires fully understanding long-term irradiation mechanisms and their effects on components such as the reactor pressure vessel (RPV). The research community is collecting data that will be required to support the case for the extended operation of western-type NPPs to beyond 60 years. One of the current issues regarding the long-term operation of RPVs is the formation of so-called late-blooming phases or MnNi-rich clusters (MNPs). The formation mechanisms of these features under irradiation, and their influence on material degradation at high neutron fluence (φt), are still unclear. The LONGLIFE project (Contract No. 249360), a EURATOM FP7 project supported by the European Commission, was designed to examine the effect of long-term irradiation on the embrittlement of RPV steels. In this paper, microstructural examinations of two low-copper welds, with different nickel contents, neutron irradiated up to about 5 × 1019 n cm-2(E > 1 MeV), are reported. Transmission electron microscopy and high-angle angular dark field scanning transmission electron microscopy (HAADF) investigations provide evidence of a very high number density of irradiation-induced nanometer-scale clusters. HAADF image data indicate that the features have a lower average projected atomic number or density than the matrix. These results are consistent with the atom probe tomography data, which demonstrate that these clusters contain high levels of manganese, nickel, and silicon. The cluster chemistries of these clusters that were detected from two different weld metals were almost identical and were similar to the chemistry of the MNPs. The cluster number density of the weld metal with more copper and nickel was found to be higher.